Competency-based education: between reality and aspirations. A field study on a sample of middle school teachers. - djenan, cherifa; boufej, wissam (sports creativity, 2025)
In this study, we addressed the topic of education in Algeria, which has undergone a series of reforms, the latest of which was education based on the competency-based approach. Our aim is to reveal the reality of education based on the competency-based approach and the extent to which it achieves educational goals. To confirm this, we conducted a field study on a purposive sample consisting of (30 middle school teachers) distributed across two middle schools. We relied on the descriptive method and used two tools: observation and a questionnaire, with its psychometric properties calculated. The following results were obtained: Education based on the competency-based approach helped achieve some goals related to student competence and effectiveness within the classroom, despite the absence of the necessary material and physical conditions to achieve all the goals.